1995
DOI: 10.1002/j.1556-6676.1995.tb01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Projective Techniques in the Counseling Process

Abstract: Projective techniques have a lengthy and vital history in personality assessment, but they have evoked a minimal degree of interest on the part of counselors. Psychometric limitations, lack of training opportunities, and the obscure qualities of the instruments have restricted their use among practitioners. The author proposes a method to stimulate the use of projectives as an integral part of the counseling process and provides justification for the expanded use of the technique as a counseling tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The following case description, derived from a comprehensive psychological assessment (Clark, 1995(Clark, ,2001(Clark, ,2002, provides a counseling example of the three ways of knowing.…”
Section: Subjective Way Of Knowingmentioning
confidence: 99%
“…The following case description, derived from a comprehensive psychological assessment (Clark, 1995(Clark, ,2001(Clark, ,2002, provides a counseling example of the three ways of knowing.…”
Section: Subjective Way Of Knowingmentioning
confidence: 99%
“…Where projective techniques are introduced at an early stage in group discussions, the responses they generate can provide ideas and new perspectives for further discussion . Clark (1995) suggested that they could be used in the counselling process for similar reasons.…”
Section: Versatilitymentioning
confidence: 99%
“…Market researchers tend to focus on the needs of the client and the needs and anxieties of respondents have rarely been subject to investigation. Clark (1995), working from a counselling perspective, identi es few dif culties and argues that clients' defensiveness often diminishes with projective techniques because of their ambiguous, absorbing and non-threatening nature. We consider that there is little to be gained from concealing the nature or purpose of projective techniques from respondents.…”
Section: Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, although this approach uses both clinical experience and intuitive acumen, it becomes difficult to document findings or to adapt procedures for instructional purposes. One way to approach this dilemma is to consider early recollections as a counseling tool that yields specific hypotheses that may subsequently be supported or refuted by data from contextual sources, such as objective and projective measures; reports elicited from a parent, teacher, spouse, or other sigruficant person; and dream material (Anastasi & Urbina, 1997;Clark, 1994Clark, ,1995Clark, ,1999.…”
Section: Uniquenessmentioning
confidence: 99%